Late Paleozoic and Early Mesozoic rare-metal granites in Central Mongolia and Baikal region: review of geochemistry, possible magma sources and related mineralization - Antipin,V.; Gerel,O.; Perepelov,A.; Odgerel,D.; Zolboo,T. (Journal of Geosciences, 2016)
The Central Asian Orogenic Belt (CAOB) was a scene of intense granitoid magmatism during the Phanerozoic with formation of vast batholiths: Angara-Vitim and Daurian-Khentei. In the Late Paleozoic and Early Mesozoic times, the peripheral zones of batholiths underwent granitic magmatism associated with rare-metal mineralization. Petrological and geochemical studies show that the rare-metal Li-F granites formed, with a gap about 100 My, large igneous provinces of the Mongol-Okhotsk Belt.Late Paleozoic rare-metal granites build a series of multiphase plutons in the Baikal region (e.g. Kharagul 318 ± 7 Ma, Bitu-Dzhida 311 ± 10 Ma and Urugudei 321 ± 5 Ma). The early medium-grained biotite granites and leucogranites, were followed by topaz-bearing microcline- and amazonite-albite granites and a series of dikes. The Early Mesozoic epoch was marked by the formation of the Daurian-Khentei Batholith (230-190 Ma) in the center of area and rifting zones with alkaline and rare-metal granite plutons on the peripheries. In contrast to the Late Paleozoic, small Early Mesozoic intrusions (e.g., Avdar Pluton ˜10 km2, 212-209 Ma) of rare-metal Li-F granites within the Avdar-Khoshutul series of granitoids coexisted with sizable plutons (e.g., Janchivlan Pluton ˜70 km2, 227-195.3 Ma). Rare-metal Li-F granites of the Janchivlan Pluton produced small domal intrusions composed of microcline-albite, amazonite-albite and albite-lepidolite granites. The Sn-Ta-Nb mineralization is associated with albite-lepidolite granites.The rare-metal granites of the Baikal region and central Mongolia of contrasting ages show an identical geochemical signature of Li-F granites. It is expressed by increase in F, Li, Rb, Cs, Sn, Be, Ta and Pb and decrease in Sr, Ba, Zn, Zr, Th and U contents in course of multiphase intrusions formation. The geochemical data confirm the magmatic model for genesis of the studied rare-metal Li-F granites. However this process of magma differentiation was terminated with formation of albitites, microclinites and muscovite greisens. The whole-rock geochemistry and isotopic composition of the granites points to the Precambrian crust of the Baikal region (T2DМ = 1.0-1.3 Ga) as the most likely source. We propose the formation of the initial granitic melts due to anatexis of the higher levels of the continental crust, with fluids released during granulite-facies metamorphism in the lower crust. The rare-metal Li-F granites of the studied provinces are intraplate formations geochemically different from the Early Paleozoic collision granitoids. This could be caused by the influence of deep-seated source on the occurrence of rare-metal magmatism.
Keywords: rare-metal granites; Li-F granite; Late Paleozoic; Early Mesozoic; Mongolia; Baikal region